Biologia e consumo alimentar de Orius insidiosus (Say, 1831) (Hemiptera: Anthocoridae) sobre duas presas diferentes - Rezende, Márcia Ferreira de Oliveira (1990)
This research aimed at studying the biology of the predator Orius insidiosus (Say 1831) (Hemiptera:Anthocoridae) on two different preys, FranklinielIa insularis (Thysânoptera: Thripidae) and eggs of Spodoptera frugiperda (Lepidopteras Noctuidae) and evaluating the feeding intake of this predator on the preys. The studies were carried out in the Entomology Laboratory at ESAL - Lavras, MG, in climatic chambers with temperature of 25 ± 1°C, relative humidity of 60 ± 10%, 15 hours of photophase and plants of Bidens pilosa as oviposition substrate. Biological traits from the egg, nymph and adult stages as well as ethological aspects of ninph and adults were studied. The nymphal phase of O. insidiosus presented five instars,for both preys, and lasted longer to develop when feeding was on S. frugiperda eggs. It was also observed that in general O. insidiosus preyed significanthy more thrips and the females feeded on this prey leyed a larger number of eggs than females feeded on S. frugiperda eggs. It was concluded that for both preys studied F. insularis is more suited for rearing O. insidiosus since it resulted in greater fecundity of the females.